Multiscale analysis of processes in complex media - Jäger, Willi; Neuss-Radu, Maria (Reactive flows, diffusion and transport, 2007)
In this report we present results concerning the study of processes in complex media. Starting from model equations at microscopic level and using the techniques of the multi-scale analysis, we determine macroscopic descriptions for reactive flow in porous media, flow at interfaces between free flow and filtration flow, flow along rough boundaries and flow through a network of channels.